INTERPERSONAL FUNCTIONS OF THE ENGLISH QUOTES OF MOTIVATION AND THEIR INDONESIAN TRANSLATIONS - Widiastuti, Ni Made Ayu; Rahayuni, Ni Ketut Sri (Lire Journal (Journal of Linguistics and Literature), 2024)
This study aims to identify and analyze the mood and modality as the parts of interpersonal metafunction in translation of the English quotes of motivation into Indonesian. The documentation method was applied to collect the source and target language quotes in the forms of clauses, simple or complex sentences. Close reading technique is applied while collecting the quotes to understand the context of the motivational expressions. The collected data were qualitatively analyzed. In order to identify the translation of English quotes of motivation into Indonesian, the parts of sentence structures in the source and target languages were compared. Contrastive linguistics is relevant for this study in order to identify the difference between both languages. The mood and modality as the interpersonal function of the Systemic Functional Linguistics (SFL) developed by Halliday were applied in analyzing the quotes of motivation. The quotes of motivation in English show the indicative mood, and so do their translations. There are 27 quotes of motivations found. All the quotes belong to the indicative mood, but there is only one quote that has the combination between indicative mood and imperative mood. Indicative mood consists of two sub-categories, they are declarative and interrogative. There is one quote started by a declarative statement, and then followed by the interrogative form, and the rest are declarative sentences. From the modality macro-function, there are eleven quotes in the forms of modal verbs. The quotes of motivation as the modality type show probability since it is given for a specific situation, and it is not used regularly. As the modulation type, it shows the obligation. In terms of the modality values, the high value is used more often than the median value. Most of the translations show similar modality types and modality values, however, there are only two quotes that show different modality types but the same modality values. The change is from the modalization type of probability ‘should’ to the modulation type of obligation ‘must’. The modality type shift does impact the reader’s understanding.